PENERAPAN INTERNET OF THINGS (IOT) UNTUK OPTIMASI PEMELIHARAAN TANAMAN RUMPUT RAJA SECARA REAL-TIME - Manalu, Andi Setiadi; Sugara, Heru; Siregar, Victor Marudut Mulia (Politeknik Bisnis Indonesia, 2024)
This study aims to optimize the maintenance of King Grass plants by utilizing Internet of Things (IoT) technology for real-time monitoring. King Grass is known as a source of livestock feed with high productivity, but its maintenance often faces challenges such as environmental fluctuations and inefficient irrigation patterns. This study uses an ESP32 microcontroller integrated with a DHT22 sensor, soil moisture sensor, and automatic water pump, and utilizes the Thingsboard platform to monitor data in real time. The data collected includes air temperature, air humidity, and soil moisture, which are displayed through interactive widgets. The system was tested by simulating various environmental conditions, showing success in automating irrigation based on soil moisture thresholds. The test results show that IoT technology is able to improve plant maintenance efficiency, reduce manual intervention, and ensure optimal conditions for plant growth. The use of the Thingsboard platform facilitates data monitoring and analysis for further planning. This study concludes that the application of IoT to King Grass maintenance provides an effective solution in increasing agricultural productivity through accurate and efficient monitoring and control.